The Role of Peers in the Social-Emotional Development of Gifted Children in Early Childhood Education - Putri, Shifa; Syafril, Syafrimen; Mulya, Neni; Wijaya Kuswanto, Cahniyo (Murhum : Jurnal Pendidikan Anak Usia Dini, 2025)
This study examines the role of peers in the social-emotional development of gifted and talented children. The Systematic Literature Review (SLR) method was used to search international databases such as Scopus, Springer, Elsevier, Taylor and Francis Online, and Google Scholar. A total of 8 studies from several countries, such as Sweden, Iran, Switzerland, and the United States, were found in the initial search. In addition, five studies that specifically addressed the role of peers in the social-emotional development of gifted and talented children were found in Brazil, Korea, and Turkey, and one book from New York State, USA. Thematic analysis was conducted with the help of NVivo 12 software to identify recurring patterns and significant themes. The study results show that peer relationships significantly affect the emotional well-being of gifted children by enhancing their self-confidence, social competence and emotional resilience. Supportive peer interactions help reduce feelings of isolation and lay the foundation for developing critical social-emotional skills such as empathy, emotion regulation, communication and collaboration. These findings emphasise that positive peer connections are critical in promoting healthy social-emotional growth. Therefore, deliberate efforts are needed to create inclusive and supportive social environments to foster the holistic development of gifted children.